The Reliability Analysis of a Turbine Rotor Structure Based on the Kriging Surrogate Model - Haiwei Lin; Liang Yang; Hong Bao; Feng Zhang; Feifei Zhao; Chaoxin Lu (Machines)
The turbine rotor is a core component in many energy conversion systems, where it is subjected to loads such as aerodynamic and centrifugal forces that make it highly susceptible to damage. Consequently, the reliability of the turbine rotor ranks among the key aspects of concern. This paper proposes an efficient approach based on the kriging model to conduct the reliability analysis of a turbine rotor. First, a parametric model of the turbine rotor was established. This parametric model was subsequently applied in a multifactor fluid–structure interaction model used to analyze the working performance of the turbine rotor. Finally, a kriging surrogate model was built and applied using these data in combination with various reliability analysis methods to analyze the structural reliability and reliability sensitivities of the turbine rotor. Furthermore, the reliability sensitivity results indicated that the outlet pressure had the greatest impact on rotor reliability. Thus, the proposed method was shown to have practical application value in the reliability analysis of the rotor structure.